PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2010 - Hermi Hermi; Ary Kurniawan (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2011)
This study aims to determine the effect of financial performance (return on the investments (ROI), Return on Equty (ROE), Net Profit Margin (NPM), Earning Per Share (EPS), Price to Book Value (PB V)) to return the shares either partial or simultaneously. The study focused on manufacturing comanies listed in Indonesia Stock Exchange (BEI) in the period 2008 to 2010. The selection of samples based on purposive sampling, so that the obtained sample of 56 manufacturing companies. The result of the sestudies show that partially only variable that has just EPS significantly influence on stock returns. While other variables, namely ROl, ROE, NPM, PBV had no signfficant effect on stock returns. In simultaneoualy free variabrl ROI,ROE, NPM, EPS, PBV has a significant effect on the stock Return.